Osteoporosis/osteopenia as an independent factor associated with periodontitis in postmenopausal women: a case–control study - Passos, J. S. (2012)
This study investigated whether osteoporosis/ osteopenia has an influence on the progression of periodontitis in postmenopausal women. The findings highlight that postmenopausal women with osteoporosis/osteopenia had a greater chance of presenting periodontitis than those with normal bone mineral density, particularly among nonusers of osteoporosis medications and women with a greater number of remaining teeth, showing that osteoporosis/osteopenia has had an influence on the progression of periodontitis. Introduction This study investigated whether osteoporosis/ osteopenia has an influence on the progression of periodontitis in postmenopausal women and explored the effects of use of osteoporosis medication and tooth loss on this association. Methods This case–control study involved 521 postmenopausal women, with minimum age of 50 years, in Feira de Santana, Bahia, Brazil. Sociodemographic characteristics, health conditions/medications, and lifestyle habits were recorded. A complete periodontal examination was performed and periodontitis was diagnosed. Bone mineral density was evaluated through lumbar spine and femoral bone densitometry, obtained using dual-energy X-ray absorptiometry. Logistic regression was used to calculate the strength of association between the occurrences of osteoporosis/osteopenia and periodontitis. Results Women with osteoporosis/osteopenia were twice as likely to present periodontitis, as were those with normal bone mineral density, even after adjusting for smoking, age, family income, and last visit to dentist (odds ratios (OR)adjusted02.24, 95 % CI [1.24–4.06], p00.008). Among nonusers of osteoporosis medication (ORadjusted02.51, 95 % CI [1.33–4.73], p00.004) and women with at least 10 remaining teeth (ORadjusted02.50 95 % CI [1.18–5.27],p00.02), the odds ratio was higher and statistically significant.